ANALISIS KELAYAKAN BISNIS PADA USAHA NITASYASCARF - Shalihah, Annisaa’ Siti; Nur Aziza, Syalma Alisa; Reynanti, Intan; Perwito, Perwito (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
The hijab industry in Indonesia continues to grow along with the increasing need for Muslim women for products that are both sharia and modern. Nitasyascarf focuses on providing quality hijabs with fashionable designs and affordable prices. This study aims to analyze the feasibility of the Nitasyascarf business through a study of market, management, production, and financial aspects. The research methods used include secondary data analysis from the literature. The results of the analysis show that this business is feasible to run with a monthly net profit projection of IDR 7,500,000, a B/C ratio of 2.30, and a realistic break-even point (BEP) target of 763 units. With a digital marketing strategy and operational efficiency, Nitasyascarf has great potential to grow in the competitive hijab industry.